Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Berbasis Masalah Di Kelas XI SMA PGRI 1 Pontianak - Sariani, Novita; Mulyanto (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
The best way to convey various concepts taught to students affects the ability to remember the concept longer. A teacher must be able to communicate effectively with students. So that a student can open their minds with different levels of intelligence. This study aims to improve student learning outcomes through problem-based learning models in class XI of SMA PGRI 1 Pontianak. The research method used is classroom action research which is carried out in two cycles. Data collection techniques use observation and test questions. The results of the study indicate that the application of problem-based models can improve student learning outcomes in class XI of SMA PGRI 1 Pontianak. There is a significant increase between cycle 1 and cycle 2. This is evidenced by the increase in the average value of student learning outcomes from cycle 1 having an average of 78.76%, the results continued to cycle 2 having an average value of 81.68% with the results of the complete category reaching the success indicator. So based on the results of the geography learning test, students have increased. This increase is supported by the results of observations and test results that students become more active, creative, and think critically and have a better understanding in the geography learning process